(E)-2-(4-Arylbut-1-en-3-yn-1-yl)chromones as synthons for the synthesis of xanthone-1,2,3-triazole dyads - Albuquerque, Hélio (2015)
Xanthone-1,2,3-triazole dyads have been synthesized by two different approaches, both starting from novel (E)-2-(4-arylbut-1-en-3-yn-1-yl)chromones, prepared through a base-catalyzed aldol reaction of 2-methylchromone and arylpropargyl aldehydes. In the first method, the xanthone moiety is built by Diels-Alder reaction of the referred unsaturated chromones with N-methylmaleimide under microwave irradiation, followed by oxidation of the obtained adducts with DDQ, whereas the 1,2,3-triazole ring results from the cycloaddition reaction of the acetylene moiety with sodium azide. The second strategy first involves the cycloaddition reaction with sodium azide to provide the 1,2,3-triazole ring, followed by methylation of the triazole NH group prior to Diels-Alder reaction with N-methylmaleimide. The last step in this synthesis of novel xanthone-1,2,3-triazole dyads entails oxidation of the cycloadducts with DDQ.